PENGARUH KINERJA KEUANGAN DAN ECONOMIC VALUE ADDED TERHADAP RETURN SAHAM PADA PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA - Awaluddin .; Shofwan Andri; Ramadona Simbolon (Universitas Islam Islam Sumatera Utara, 2021)
The purpose of this study is to prove the relationship between return on assets and economic value added with stock returns in pharmaceutical sector companies listed on the Indonesia Stock Exchange, from 2017 to 2019. Sampling was carried out by purposive sampling, and there were 6 companies used as samples. as research samples from 10 companies. The source of data in this study is secondary data obtained from the Indonesia Stock Exchange. Data were analyzed using multiple linear regression. The results of this study provide evidence that individually, return on assets has a positive and significant effect on stock returns, and economic value added does not have a significant effect on stock returns. Meanwhile, simultaneously return on assets and economic value added have a positive and significant effect on stock returns.